Application of the Orem Self Care Theory in the Assessment of Mothers with Severe Preeclampsia with Electrolyte Disorders: Case Study - Irma Rachmawati; Windy Natasha; Ermiati Ermiati; Restuning Widiasih (Indonesian Journal of Global Health Research, 2024)
One of the causes of maternal death is uncontrolled complications of severe hypertension. In preeclampsia, the risk to the fetus is very high, such as delayed intrauterine growth, prematurity and intrauterine death. Signs and symptoms of severe preeclampsia should be used as an "alarm" by pregnant women with severe preeclampsia to prevent eclampsia. The aim of monitoring symptoms in severe preeclampsia is to avoid unwanted maternal or fetal complications. Case Mrs. M. age 33 G3P1A1 gravida 31 weeks 0 days, Patient is known to have had high blood pressure since 7.5 months of pregnancy, history of eclampsia, BP 153/105 mmHg, Potassium (2.2), Calcium ion 4.52. Based on this study case, the patient experienced hypokalemia and hypocalcemia, the concept of Orem self-care theory can be applied in identifying or assessing cases of severe preeclampsia in monitoring signs and symptoms of severe preeclampsia by recognizing the signs and symptoms. Orem's self-care theory makes individuals responsible for their own care which is part of awareness of the importance of maintaining the health of themselves and the fetus in their womb. Based on symptoms, patients can use assessment with a self-care approach to prevent eclampsia and HELLP syndrome.